Technology-based therapy-response evaluation of axial motor symptoms under daily drug regimen of patients with Parkinson’s disease - Wu, Zhuang; Hong, Ronghua; Li, Shuangfang; Peng, Kangwen; Lin, Ao; Gao, Yichen; Jin, Yue; Su, Xiaoyun; Zhi, Hongping; Guan, Qiang; Pan, Lizhen; Jin, Lingjing (Frontiers in Aging Neuroscience, 2022)
Background: Axial disturbances are the most disabling symptoms in Parkinson’s Disease (PD). Kinect-based objective measures could extract motion characteristics with high reliability and validity. Purpose: The present research aimed to quantify the therapy-response of axial motor symptoms to daily medication regimen and to explore the correlates of the improvement rate (IR) of axial motor symptoms based on Kinect camera. Methods: We enrolled 44 PD patients and 21 healthy controls. All 65 participants performed Movement Disorder Society-Sponsored Revision of the Unified Parkinson’s Disease Rating Scale part Ⅲ and Kinect-based kinematic evaluation to assess arising from a chair, gait, posture and postural stability before and after medication. Spearman correlation analysis and multiple linear regression model were performed to explore the relationships between motor feature IR and clinical data. Results: All the features of arising from a chair (P=0.001), stride length (P=0.001), velocity (P<0.001), the height of foot lift (P<0.001) and turning time (P=0.001) improved significantly after daily drug regimen in PD patients. In addition, anterior trunk flexion (lumbar level) exhibited significant improvement (P=0.004). The IR of axial motor symptom score was significantly correlated with the IRs of kinematic features for gait velocity, stride length, foot lift height and sitting speed (rs=0.345, P=0.022; rs=0.382, P=0.010; rs=0.314, P=0.038; rs=0.518, P<0.001, respectively). Multivariable regression analysis showed that the improvement in axial motor symptom was associated with the IR of gait velocity only (β=0.593, 95% confidence interval=0.023-1.164, P=0.042). Conclusion: Axial symptom was not complete drug-resistant and some kinematic features can be improved after daily medication regimen of PD patients.